Effects of Robotic Coding on Computational Thinking Skills of Secondary School Students - Altıok, Serhat; Üçgül, Memet (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
In recent years, computational thinking has garnered increased attention as an essential problem-solving skill. One of the methods to develop students’ computational thinking skills is robotic coding activities. This study sought to investigate the impact of robotic coding activities on the self-efficacy perceptions of secondary school students’ computational thinking skills. A one-group pretest-posttest quasi-experimental design was employed, involving 32 secondary school students. These students, organized in groups of four, engaged in hands-on robotic coding activities using Lego Mindstorms EV3 Education robots over a total of 20 hours. Data were collected before and after the robotic coding activities using the Self-Efficacy Perception Scale for Computational Thinking Skills (SEPSCTS) instrument, comprising 36 items categorized into five factors. The data were analyzed using paired samples t-tests and analysis of covariance (ANCOVA). The results demonstrated a significant increase in students’ self-efficacy perceptions of computational thinking skills following the activities, with this increase observed consistently across genders. Finally, the challenges encountered during research and practice were reported, along with the study’s limitations, to inform future research endeavours.